تراجع فكرة الخطأ في المسؤولية المدنية - إسماعيل, المهدي مراجع (Tobruk University Journal of Social and Human Sciences, 2023)
The element of error in civil responsibility in general has become a renewed topic, worthy of study and research. The increase and diversity of accidents in our current reality has prompted the idea of abandoning error, and removing it from the traditional situation to become a modern topic that needs in-depth study. In view of the unfairness of the fault as a basis for civil liability, vigorous judicial efforts have been made, and jurisprudence has begun to attack the theory of fault. This development coincided with the issuance of self-contained legislative systems such as insurance and compensation funds, so that jurisprudence found a fertile ground for striving and proposing new foundations for civil responsibility.